Zarządzanie projektami współfinansowanymi ze środków unijnych w przedsiębiorstwach dolnośląskich - Krzos, Grzegorz (Project management co-financed by the UE funds implemented in Lower Silesian enterprises, 2007)
The main goal of this article is to present results of the pilot research work in 113 Lower Silesian enterprises on the scalę of the project management method used in the process of funds absorption for company development from the European Union. One of the goals in this research work was the assessment of effectiveness of obtaining the EU grants by SME in the years 2004 and 2005. The research focused on the way the enterprises use the methodology and instruments of project management in the process of obtaining grants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 287-298